SHIFTING THE DISCOURSE: STUDENT DEPARTURE IN THE CONTEXT OF RELATIVE DEPRIVATIONS - manik, sadhana (South African Journal of Higher Education, 2016)
Student departure from higher education has become a scourge undermining efforts to increase throughput at institutions in post-apartheid South Africa. It is largely viewed through a national/institutional ‘rates’ lens. When students have been participants in studies their voices have been subdued methodologically. This article reports on the causes of student departure by foregrounding students’ voices. It draws on qualitative data from a study at a KwaZulu-Natal higher education institution. The findings comprise institutional career derailment, lack of counselling, financial requirements, and academic work demands. Collectively they indicate student relative deprivations, signalling the need for greater institutional engagement with students to address their needs. The article argues for the institution to include and expand safety nets for students, especially increased, effective support personnel to overcome the culture of student silence when experiencing stresses. KEYWORDS: finance, work demands, counselling, relative deprivations